Evaluating the effect of cognitive-behaviourally informed artificial intelligence coaching on the development of leader character: A mixed-methods randomised controlled study - Van der Walt, Liesl (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.